Adaptive Switching Scheme Design Using Ceiling Function for Discrete-Time Sliding Mode Control - Pandey V.; Singh V.K.; Taslima E.; Kamal S.; Ghosh S. (My University, 2025)
The adaptive reaching law for uncertain discrete-time systems is discussed in this research article, and a novel method for controlling discrete-time systems with matched uncertainties and disturbances is presented. In this research, the control gains of the controller are adaptively adjusted using the minimum operator and ceiling function. The technique also provides the opportunity to select the reaching time for the sliding surface, and the law guarantees that the system reaches a sliding surface within a predetermined time. By adopting a non-switching-type definition of sliding motion, unwanted chattering effects during the sliding phase are also avoided by this method. Sliding-mode dynamics are theoretically analyzed, and two examples are provided to validate the proposed method. © 2024 IEEE.